Staten Island Stories - Jimenez, Claire (Book collections on Project MUSE., 2019)
"This collection of tragicomic short stories, whose form is inspired by Geoffrey Chaucer's The Canterbury Tales, feature various inhabitants of Staten Island, New York City's so-called forgotten borough. The collection travels across time through the voices of working-class folks to explore defining moments in the island's history and in US history"--